Focusing of electron bunches in the plasma-dielectric rectangular slowing-down structure - Markov, P.I.; Kniaziev, R.R.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2016)
Results of analytical and numerical researches of excitation of wakefield and dynamics of the charged particles
in the plasma-dielectric rectangular slowing-down structure are provided. Based on that the analytics in linear approach
for overdense plasma shows that at the certain density of plasma the superposition of plasma and dielectric
waves allows to accelerate test bunch with its simultaneous focusing, we have made simulation by the "particle in
cell" method of excitation of wakefield for several cases with different plasma density. The carried-out numerical
modeling has confirmed predictions of the analytical theory, having shown an acceleration of test bunch with its
simultaneous focusing. Представлены результаты численных исследований возбуждения кильватерных полей и динамики заряженных частиц в плазменно-диэлектрической прямоугольной замедляющей структуре. Основываясь на том,
что аналитика в линейном приближении для сверхплотной плазмы показывает, что при определенной плот-
ности плазмы суперпозиция плазменной и диэлектрической волн позволяет ускорять тестовый сгусток с его
одновременной фокусировкой, мы выполнили моделирование методом “частица в ячейке” возбуждения
кильватерных полей для нескольких случаев с разной плотностью плазмы. Проведенное численное моделирование подтвердило предсказания аналитической теории, продемонстрировав ускорение тестового сгустка
с одновременной его фокусировкой. Представлено результати чисельних досліджень збудження кільватерних полів і динаміки заряджених
часток у плазмово-діелектричній прямокутній сповільнюваній структурі. Ґрунтуючись на тому, що аналітика в лінійному наближенні для надщільної плазми показує, що при певній щільності плазми суперпозиція
плазмової й діелектричної хвиль дозволяє прискорювати тестовий згусток з його одночасним фокусуванням,
ми виконали моделювання методом “частинка у гнізді” збудження кільватерних полів для декількох випадків з різною щільністю плазми. Проведене чисельне моделювання підтвердило пророкування аналітичної
теорії, продемонструвавши прискорення тестового згустка з одночасним його фокусуванням.